2004
DOI: 10.1074/jbc.c400239200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1 Associates with the Integrin αIIb Subunit and Regulates Signaling

Abstract: Regulation of integrin activation occurs by specific interactions among cytoplasmic proteins and integrin ␣ and ␤ cytoplasmic tails. We report that the catalytic subunit of protein phosphatase 1 (PP1c) constitutively associates with the prototypic integrin ␣ IIb ␤ 3 in platelets and in cell lines overexpressing the integrin. PP1c binds directly to the cytoplasmic domain of integrin ␣ IIb subunit containing a conserved PP1c binding motif 989 KVGF 992 . Anchored PP1c is inactive, while thrombininduced platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 28 publications
3
58
0
Order By: Relevance
“…This observation is consistent with a previous study that showed an association of the inhibitor for PP2A (I1PP2A) with the membrane proximal GFFKR motif of integrin ␣ 3A ␤ 1 (24). The membrane proximal region of ␣ IIb can host the binding of calcium and integrinbinding protein 1, PP1c, and ICIn (8,25,26); therefore, it is conceivable that only a subpopulation of ␣ IIb ␤ 3 may harbor PP2Ac. Because GFFKR sequence is conserved in other ␣ subunits, it is likely that PP2Ac association may not be limited to ␣ IIb subunits.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This observation is consistent with a previous study that showed an association of the inhibitor for PP2A (I1PP2A) with the membrane proximal GFFKR motif of integrin ␣ 3A ␤ 1 (24). The membrane proximal region of ␣ IIb can host the binding of calcium and integrinbinding protein 1, PP1c, and ICIn (8,25,26); therefore, it is conceivable that only a subpopulation of ␣ IIb ␤ 3 may harbor PP2Ac. Because GFFKR sequence is conserved in other ␣ subunits, it is likely that PP2Ac association may not be limited to ␣ IIb subunits.…”
Section: Discussionsupporting
confidence: 80%
“…In resting platelets, a pool of the catalytic subunit of protein phosphatase 1 (PP1c) constitutively associates with ␣ IIb ␤ 3 complex (8). Studies from other cell types have revealed that PP2Ac can associate with integrin ␤ 1 (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, fostriecin had no effect on the elevation of p38 MAPK phosphorylation found in Pro33 cells, though the PP1/PP2A inhibitor okadaic acid was effective. Thus, we suspect that PP1 activation downstream of Pro33 may be responsible for p38 MAPK activation, whereas transmission of kinase activation to SERT upregulation involves PP2A ( Figure 6C) (34). Student's t test: *P < 0.05; 1-way ANOVA with Dunnett's post-test: # P < 0.05; n = 6.…”
Section: Discussionmentioning
confidence: 99%
“…PP2A, in turn, plays a critical role in αIIbβ3-mediated cell adhesion Integrin mediated cell adhesion is known to induce changes in PP2A activity [18] and localization within integrin-organized focal adhesion complex through its interaction with paxillin [19]. Instructively, the activity of αIIbβ3 has been shown to regulate phosphatase PP1 [20]. The association of both PP1 and PP2A with αIIb and β3, respectively, highlights the importance of phosphatases in the regulation of integrin signaling.…”
Section: Discussionmentioning
confidence: 99%